Association between the systemic immune-inflammation index and sarcopenia in older adults: a cross-sectional study - Esra Cataltepe; Eda Ceker; Ayse Fadiloglu; Fatih Gungor; Nermin Karakurt; Zekeriya Ulger; Hacer Dogan Varan (BMC Geriatrics)
Abstract Background Chronic inflammation is increasingly recognized as a crucial contributor to sarcopenia pathogenesis, but accurate diagnosis remains a challenge. Aim Our study aims to investigate the relationship between sarcopenia and the Systemic Immune-Inflammation Index (SII), a comprehensive indicator of inflammation. Methods This cross-sectional study enrolled 632 patients. All participants underwent a comprehensive geriatric assessment. Sarcopenia was assessed through the evaluation of handgrip strength and calf circumference. To determine the SII, we used the formula: Platelet count (109/mm3)×Neutrophil count (109/mm3) / Lymphocyte count (109/mm3). Results The average age of the participants was 74.8 ± 6.4, and 62.3% (n = 394) were female. Patients were grouped as non-sarcopenic and sarcopenic. The non-sarcopenic group had 536 patients (84.8%), while the sarcopenic group comprised 96 patients (15.2%). Sarcopenic patients showed a higher median SII score than the non-sarcopenic group (p < 0.001). Multivariate logistic regression analysis revealed that the SII score was significantly and independently associated with sarcopenia even after adjusting for potential confounding factors (β = 1.002, 95% CI = 1.001–1.003, p < 0.001). The ROC analysis identified the optimal cut-off for SII in predicting sarcopenia as > 765. At this threshold, the negative predictive values were determined to be 88.1%, with a specificity of 88%. Conclusion SII is significantly associated with sarcopenia in a geriatric outpatient population, and a population-specific SII cut-off may serve as a novel, simple, and practical biomarker for diagnosing sarcopenia.